Interior Setting as A Time Indicator on “Sabtu Bersama Bapak” The Series : - - Marlief, Arasya Salshabila; Setiawati, S.Sn., M.Sn, Sri Wastiwi (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
This study uses interior settings as time indicators in the series Sabtu Bersama Bapak. The main objective of this study is to describe the artistic elements found in the interior settings, especially decorations and properties, which represent a certain period in the visual narrative. This study uses a qualitative descriptive method to produce a structured, detailed, and in-depth explanation of how visual elements play a role in strengthening the temporal context of the story. The analysis was carried out on several main settings in the series, namely the 1980s setting represented through Itje's house and Pak Edi's house, the 1990s setting shown in Gunawan's house, and the 2022 setting seen in Saka's office and Satya's house. Through this approach, the study aims to provide insight into the importance of the accuracy and precision of visual details as an integral part of building the atmosphere of the era, while strengthening the narrative power in film and television production.